A Comparison of Natural Eimeria spp. and Gastrointestinal Nematode Infections of Goat Breeds - Cemil Tölü; Türker Savaş (Journal of Agricultural Sciences)
The number of Eimeria oocysts per gram faeces OPG and number of gastrointestinal nematod GIN eggs per gram faeces EPG depend on some factors such as gender, season and production systems. In order to determine the Eimeria infection and some gastrointestinal nematode burdens in Maltese, Gökçeada and Turkish Saanen goats, OPG, EPG and packed cell volume PCV were investigated. Maltese breed tended to have lower parasite burden than other goat breeds P≤0.05 . In the first observation, the prevalence of Eimeria and nematodes was 100% in Gökçeada breed, while the prevalence of Eimeria and the prevalence of GIN infection were 98% and 78%, respectively, in Maltese. It was determined that OPG and EPG burdens were significantly affected by the age of goats and the sampling date P≤0.0193 . It was seen that OPG burden decreased as the goats get older P= 0.0157 , while EPG value varied by the age of a goat in an unsteady manner P